OBB a.k.a The original brown boy / Paolo Javier with art by Alexander Tarampi & Ernest Concepcion. - Javier, Paolo, 1974- (Nightboat Books, 2021)
"OBB a.k.a. The Original Brown Boy has many identities: it is a comics poem and a manifesto on comics poetry; an experimental comic book sequel to a poem twenty years in the making; and an homage to the Mimeo Revolution, weird fiction, kamishibai, the political cartoon, Pilipinx komiks history, and the poet bp Nichol. Javier deconstructs a post-9/11 Pilipinx identity amid the lasting fog of the Philippine American War, to compose a far-out comic book awit"--Amazon.com.